The Causes and Efforts of Parents to Overcoming Tantrums in Early Childhood - Amalia Husna; Rakimahwati (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
One of the problems experienced by young children is tantrums. If a tantrum cannot be overcome, it can harm the child and the people around him. The child cannot control his emotions and faces problems in his environment. This research aims to analyze parents' causes and efforts in dealing with early childhood tantrums. This research is a mixed method. The research subjects were children who experienced tantrums and their parents. Data was collected by conducting surveys, interviews with parents, and observations. Data collection instrument using questionnaires. Quantitative data analysis uses percentage scores, while qualitative data analysis uses the data analysis model, according to Milles and Huberman. The research results show that the tantrums experienced by children are crying loudly, screaming/shouting, throwing or slamming things, hitting, and throwing tantrums. The causes of children having tantrums are unfulfilled desires, boredom, fighting over toys, parents pampering/protecting children too much, being bullied, or fighting with friends or relatives. Meanwhile, the efforts made by parents to deal with tantrums in children are diverting the child's attention, whispering to the children, hugging the child, letting the child calm down, recognizing the child's habits, giving the child an understanding of the level of intensity of anger; and, do not spoil children.